Regularized topology optimization for light trapping structure in solar cells - Zhang, Zijian (Frontiers in Nanotechnology, 2026)
Efficient light trapping bulk structures can significantly enhance light absorption in solar cells while reducing manufacturing costs. However, locating the optimal set of design parameters within a complex solution space remains challenging. Although numerous optimization algorithms have been employed to optimize bulk structure topologies, most treat the problem as purely mathematical, overlooking established physical principles such as light trapping and anti-reflection theories. By integrating both light-trapping and anti-reflection regularization, we obtain a 2 dimensional silicon inverted pyramid array (IPA) structure with an absorption rate of 0.7076, which yields a relative enhancement of 11.6% over the non-regularized baseline.